Dansylated estramustine, a fluorescent probe for studies of estramustine uptake and identification of intracellular targets. - Stearns, M E (1985)
Fluorescence-microscopic studies with dansylated estramustine (DnsEM) has permitted investigation of the mechanism of estramustine (EM) uptake in live human prostatic tumor cells (DU 145). DnsEM appeared to enter cells rapidly at the peripheral cell margins. A progressive increase in fluorescence was observed until the perinuclear material and cytoplasm were labeled brightly and the nucleoplasm was labeled faintly. Light microscopy showed that DnsEM is assimilated first in preexisting vesicles and then in numerous newly created vesicles that accumulate in the cytoplasm and around the nucleus. Colony-forming assays showed EM and DnsEM to be equally cytotoxic to cultured DU 145 cells. Cellular uptake and subsequent manifestation of cytotoxicity are presumably dependent upon these vesicles. However, after uptake of DnsEM, its diffusion into the cytoplasm was observed.